Mapping evidence on the regulations affecting accessibility, availability and management of snake antivenom globally: a scoping review protocol - Kabelo Kgarosi; Ramsha Majeed; Janette Bester; Morné Strydom (BMJ Open)
Introduction Snakebite envenomation has been declared a neglected tropical disease by the WHO since 2017. The disease is endemic in affected areas due to the lack of availability and access to antivenom, despite it being the standard treatment for snakebites. This challenge is perpetuated by the shortcomings of the regulatory systems and policies governing the management of antivenoms. This study aims to map the evidence about regulations of snake antivenom globally and identify gaps in the literature. This protocol provides an overview of the methodology and analysis which will be used to conduct the scoping review.Method and analysis The scoping review follows the guidelines from the Arksey and O’Malley framework for scoping reviews and will be reported using Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. A search strategy was developed with assistance from a health sciences librarian, and the search was done using six relevant databases. The databases used are PubMed, SCOPUS, ProQuest Central, Africa Wide Web, Academic Search Output and Web of Science. Articles in the English language and between 2009 and 2023 were included. The search results were collated, duplicates were removed and results were exported to Rayyan (https://www.rayyan.ai/) for screening. The initial screening for titles and abstracts is currently in progress, and thereafter the second round of screening will be done for full texts. Data extraction will be done using Google Forms. The results of the review will be synthesised using quantitative and qualitative tools.Ethics and dissemination This review will provide guidance for studies investigating regulatory gaps globally and inform future policies governing antivenom management. Ethics approval for the complete postgraduate project was obtained from the University of Pretoria Research Ethics Committee. The review will be published in a scientific journal, and findings will also be disseminated using conference presentations.Trial registration This review has been registered on Open Science Framework (OSF): https://osf.io/54zja.